2006
DOI: 10.1038/sj.sc.3101932
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of spinal cord astrocytomas

Abstract: Study design: Retrospective case series.Objectives: To analyze prognostic factors for patients with spinal cord astrocytomas. Setting: Department of Orthopaedic Surgery, Keio University, Japan. Methods: Seven patients received total excisions (group T), eight underwent partial excisions (group P), and 15 had excisional biopsies (group B). Impacts of the tumor histological grade, the level of the tumor, the types of surgical interventions, and the use of adjuvant radiotherapies on the survival and functional ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…Of these, five were classified as category A, four did not report any significant relationship between tumor location and outcome [24,28,30,34], only (8) 13 (100) 6 (46) (23) 39 (68) 10 (17) Minehan [49] found significantly ''increased'' survival in patients with thoracic spinal cord involvement. In addition, in one category B study, survival of patients with astrocytomas in thoracic location was significantly higher than in cervical location in both LG and HG tumors [51].…”
Section: Tumor Locationmentioning
confidence: 94%
See 4 more Smart Citations
“…Of these, five were classified as category A, four did not report any significant relationship between tumor location and outcome [24,28,30,34], only (8) 13 (100) 6 (46) (23) 39 (68) 10 (17) Minehan [49] found significantly ''increased'' survival in patients with thoracic spinal cord involvement. In addition, in one category B study, survival of patients with astrocytomas in thoracic location was significantly higher than in cervical location in both LG and HG tumors [51].…”
Section: Tumor Locationmentioning
confidence: 94%
“…Remarkably, radical resection of anaplastic astrocytoma was not associated with increase in postoperative decline in neurological function [46]. In addition, one category B study reported increased 10-year OS in patients receiving GTR or PR when compared to biopsy (80 vs. 32%, p = 0.0251) [51].…”
Section: Syrinx/cyst Presencementioning
confidence: 98%
See 3 more Smart Citations